Different Contexts in the Oddball Paradigm Induce Distinct Brain Networks in Generating the P300 - Li, Fali; Yi, Chanlin; Jiang, Yuanling; Liao, Yuanyuan; Si, Yajing; Dai, Jing; Yao, Dezhong; Zhang, Yangsong; Xu, Peng (Frontiers in Human Neuroscience, 2019)
Despite the P300 event-related potential differences between distinct stimulus sequences, the effect of stimulus sequence on the brain network is still left unveiled. To uncover the corresponding effect of stimulus sequence, we thus investigated the differences of functional brain networks, when a target (T) or standard (S) stimulus was presented preceding another T as background context. Results of this study demonstrated that, when an S was first presented preceding a T (i.e., ST sequence), the P300 experiencing large amplitude was evoked by the T, along with strong network architecture. In contrast, if a T was presented in advance (i.e., TT sequence), decreased P300 amplitude and attenuated network efficiency were demonstrated. Additionally, decreased activations in regions, such as inferior frontal gyrus and superior frontal gyrus were also revealed in TT sequence. Particularly, the effect of stimulus sequence on P300 network could be quantitatively measured by brain network properties, the increase in network efficiency corresponded to large P300 amplitude evoked in P300 task.